PENGARUH KARAKTERISTIK PEMDA DAN TEMUAN AUDIT BPK TERHADAP KINERJA PEMDA KABUPATEN DI PULAU SUMBA - Samuel Christian Ara; Titiek Herwanti; Endar Pituringsih (JAFFA, 2016)
This research is aimed at examining and analyzing the effect of the characteristics of the local government and BPK audit findings on the performance of local governments on the island of Sumba. Local government performance is measured by a score results of Evaluasi Kinerja Penyelenggaraan Pemerintahan Daerah (EKPPD).This research was classified as associative research. The samples used were all local governments on the island of Sumba, Sumba Timur, Sumba Tengah, Sumba Barat and Sumba Barat Daya during the period of 2009-2014. The Analysis employed multiple linear regresion.The research showed that the variable characteristics of the local government who described the wealth level of local government, the level of dependence on central government, capital expenditures and audit findings on the performance of local governments on the island of Sumba.The implications of this research theoretically contribute in the field of public sector accounting, particularly at the local government in governance. Practically provide information and advice to the local government in terms of financial management. In this research provide information policy as a basis for consideration in making policy as an effort to improve the performance of local governments on the island of Sumba.